2023
DOI: 10.3389/fmicb.2022.1086334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous cropping Jiashi muskmelon on rhizosphere microbial community

Abstract: IntroductionThe continuous cropping of crops can result in the deterioration of the soil environment and cause a decline in plant health and yield, which complicates agricultural production. However, the effects of continuous melon cropping on rhizospheric microbial communities remain poorly understood.MethodsIn this study, high-throughput absolute quantification 16S rRNA gene amplicon sequencing was employed to analyze the bacterial community structure of greenhouse rhizosphere soil from Jiashi muskmelon repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…The proportion of Chloroflexi in CC1Y was 17.38% ± 2.86%, while it decreased to 13.60% ± 1.03%, 14.77% ± 0.85%, 14.57% ± 0.57%, 14.24% ± 1.30%, 12.57% ± 1.14%, and 12.50% ± 1.42%, respectively, along with the continuous cropping years. However, compared to previous studies, it was still at a higher level (Wang et al, 2022a;Wang et al, 2022c;Yu et al, 2023). The significance test of inter group differences indicated that Chloroflexi, Firmicutes, Myxococcota, and Patescibacteria had significant differences between different samples (Supplementary Figure S2A).…”
Section: Effects Of Continuous Cropping On Soil Microbial Community S...mentioning
confidence: 66%
“…The proportion of Chloroflexi in CC1Y was 17.38% ± 2.86%, while it decreased to 13.60% ± 1.03%, 14.77% ± 0.85%, 14.57% ± 0.57%, 14.24% ± 1.30%, 12.57% ± 1.14%, and 12.50% ± 1.42%, respectively, along with the continuous cropping years. However, compared to previous studies, it was still at a higher level (Wang et al, 2022a;Wang et al, 2022c;Yu et al, 2023). The significance test of inter group differences indicated that Chloroflexi, Firmicutes, Myxococcota, and Patescibacteria had significant differences between different samples (Supplementary Figure S2A).…”
Section: Effects Of Continuous Cropping On Soil Microbial Community S...mentioning
confidence: 66%
“…For instance, Zhang et al (2018) observed a significant increase in bacterial and fungal diversity in soils amended with earthworm casts compared to control soils. The presence of diverse microbial communities in amended soils contributes to improved nutrient availability and cycling.…”
Section: Effect Of Earthworm and Its Cast On Soil Microbial Diversitymentioning
confidence: 97%
“…In addition, prolonged and uninterrupted cropping practices over several decades often result in modifications to soil properties, e.g., leading to a reduction in the levels of organic matter and essential micronutrients such as iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu) both as plant available species and bound to soil organic matter and other surfaces of the soil particles [26].…”
Section: Introductionmentioning
confidence: 99%